OPTIMASI PROSES PEMBUATAN BIODIESEL BERBANTUKAN GELOMBANG ULTRASONIK DARI BLENDING MINYAK KELAPA SAWIT (CRUDE PALM OIL) DAN MINYAK JARAK (JATROPHA CURCAS OIL) - Aji Baharsyah; S Supriyandi; Hantoro Satriadi; W Widayat (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Limitations of diesel which is a non-renewable energy sources, requires alternative fuels to renewable and environmentally friendly, for example is biodiesel. The main reaction is the production of biodiesel esterification and transesterification, but these conventional reactions are slow, requires a lot of alcohol and a catalyst, the reaction has not been perfect, and the products do not meet SNI and ASTM standards. In this research, mixing castor oil and palm oil as biodiesel feedstock, but it aims to obtain the optimum conditions for the blending ratio variable mass castor and palm oil, the amount of catalyst to oil, and the mole ratio of methanol-oil with helped by ultrasonic waves. The resulting biodiesel product is expected to meet SNI and ASTM standards. The main tool used is the ultrasonic cleaner. Variable that is the ratio of the mass of castor oil and palm 1:1, 2:1, and 3:1, the amount of catalyst KOH 1%, 1.5%, and 2% by mass of oil, and methanol-oil mole ratio 3:1, 6 : 1, and 9:1. The results obtained highest conversion achieved in the mass ratio 2:1 castor oil and palm oil, catalyst 1.5% by mass of oil, and the mole ratio of 6:1 with a mixture of methanol-conversion 95.341% where diesel fuel product meets SNI and ASTM standards.